Paket Pendidikan Kesehatan Siaga Risiko Stunting (SKORING) Terhadap Pengetahuan dan Sikap Remaja Dalam Mencegah Stunting - Natasya Violita Anggreani; Apriliani Yulianti Wuriningsih (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Stunting is a chronic nutritional problem that is influenced by various factors, such as socio-economic conditions, the mother's nutritional status during pregnancy, and lack of nutritional intake for babies. One of the main causes of stunting is inadequate nutrition. Health education related to stunting prevention (scoring) plays a significant role in increasing teenagers' knowledge and attitudes to prevent stunting, ensuring nutritious food intake, and promoting clean lifestyles by maintaining environmental sanitation and cleanliness to address the stunting issue. Purpose: The purpose of this study is to determine the effect of the stunting risk alert health education package (scoring) on adolescents' knowledge and attitudes in preventing stunting in SMA Negeri 1 Mranggen. Method: This research used a quasi-experimental method with a control group using a pre-test, intervention, post-test design. The sample consisted of teenagers from SMA Negeri 1 Mranggen, with a total of 48 respondents who were divided into a control group and an intervention group using simple random sampling. Data were obtained by having the respondents complete a questionnaire before and after the intervention, and then analyzed using bivariate and univariate sample tests. Results: The results showed a significant difference between the pre-test and post-test in the level of adolescent knowledge about stunting disease and adolescents' attitudes toward stunting before and after the intervention. There was also a noticeable difference between the intervention group and the control group. Conclusion: The stunting risk alert health education package (scoring) has a significant effect on adolescents' knowledge and attitudes in preventing stunting.